1993
DOI: 10.1136/bmj.306.6883.953
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral herniation during bacterial meningitis in children.

Abstract: Objective-To see whether the incidence of cerebral herniation is increased immediately after lumbar puncture in children with bacterial meningitis and whether any children with herniation have normal results on cranial computed tomography.Design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 7 publications
6
103
1
2
Order By: Relevance
“…27,28 There were some case series that reported outcomes after brain herniation (Table 3). [29][30][31][32][33][34][35] Unfortunately, none of these specifically commented on whether the outcomes in survivors were due to spinal cord injury. These series show that there is a high mortality after brain herniation, and that 25-50% of survivors are left with severe sequelae, including 'spastic limbs.'…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 There were some case series that reported outcomes after brain herniation (Table 3). [29][30][31][32][33][34][35] Unfortunately, none of these specifically commented on whether the outcomes in survivors were due to spinal cord injury. These series show that there is a high mortality after brain herniation, and that 25-50% of survivors are left with severe sequelae, including 'spastic limbs.'…”
Section: Resultsmentioning
confidence: 99%
“…These series show that there is a high mortality after brain herniation, and that 25-50% of survivors are left with severe sequelae, including 'spastic limbs.' [29][30][31][32][33][34][35] In one series of traumatic transtentorial herniation, cardiac arrest, flaccidity or bilateral fixed pupils after the herniation predicted worse neurological outcome. 33 We found only two case series of BD that specifically commented on the pathological findings in the spinal cord (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been under discussion for decades, originating from anecdotic cases, whether LP is associated with brain stem compression precipitating a life-threatening situation when performed in patients with increased ICP (6)(7)(8)(9)(10). An outcome study from our hospital of severe meningitis showed that in most patients developing brain stem symptoms, these appeared shortly after LP (11).…”
Section: Introductionmentioning
confidence: 99%
“…An important reason why no consensus has been reached regarding the use of LP in patients with suspected raised ICP is that no reliable scientific studies on potential adverse effects with LP have been made. As a matter of precaution, some authors recommend that LP should be avoided in patients with clear signs of raised ICP, such as progressive loss of consciousness, agitation and motor anxiety, increasing blood pressure, pupil abnormalities and other focal neurological signs (8,9,11). LP is, however, frequently used in clinical practice also in risk patients (13).…”
Section: Introductionmentioning
confidence: 99%